Intracrystalline mesoporosity over Y zeolites. Processing of VGO and resid-VGO mixtures in FCC - García, Juan Rafael (2017)
Prototypes of FCC catalysts containing 30 %wt. Y zeolite with different intracrystalline mesoporosity generated by alkaline desilication, on an inert silica matrix, were tested in cracking a conventional vacuum gasoil (VGO) feedstock, alone and mixed with an atmospheric tower residue (ATR). The experiments were performed in a fluidized bed CREC Riser Simulator reactor (reaction time: 5-30 s, temperature: 550 °C, catalyst/feedstock: 4.5). Independently of the catalyst, the conversions of the ATR-VGO mixture were higher than those of the VGO at the same conditions. With both feedstocks, the catalyst including the zeolite with increased intracrystalline mesoporosity and higher acidity showed a higher observed activity than the catalyst with the parent zeolite. In addition, the catalyst with the modified zeolite showed higher selectivity to LCO, which is an intermediate product in FCC and a contributor to the diesel pool, especially with the ATR-VGO mixture. This effect was the consequence of the enhanced diffusion transport of primary product molecules in the zeolite pore system which, in diffusing faster, have fewer chances to be further cracked. The catalyst with higher mesoporosity showed higher coke selectivity, coke being less condensed, due to the higher free volume in the porous system allowing accommodate precursors of coke.